Simulating the integration of photovoltaic technology on the modern infantry soldier using modelling and simulation: scenarios and guidelines. (April 2014) - Paraskevopoulos, Ioannis; Tsekleves, Emmanuel
The operational range and manoeuvrability of the modern infantry soldier is restricted by the overall load and bulk of equipment ranging from 50 to 75 kg. Today's soldiers rely heavily on batteries to meet their power requirements, which make up 25% of the overall load. This results in a significant increase on soldier's physical stress and cognitive burden. Recent developments in renewable energy, and more particularly the evolution of very thin and flexible wearable photovoltaic devices, provide promising solutions for the application of such technologies on the infantry soldier. However, since these flexible substrate devices are still under development or produced at a very small scale, their application and use has to be simulated prior to integrating to the infantry soldier. Such simulations need to take into account the specific requirements and different fields of operation of the infantry soldier, in the context of weather, date and time, global location and for different military mission environments. This paper presents a number of simulations performed for a wide range of scenarios in the context of the Solar Soldier project. It discusses the key results, offering a set of guidelines for the positioning and integration of such renewable energy technology on the modern infantry soldier. Moreover, this paper suggests future improvements on the methodology and optimisation of the procedures.